THERMO-ANALYTICAL COMPLEX FOR SUBSTANCES IDENTIFICATION BY THE METHOD OF DIFFERENTIAL THERMAL ANALYSIS - Дрючко, О. Г.; Стороженко, Д. О.; Бунякіна, Н. В.; Іваницька, І. О.; Голубятніков, Д. В. (Scientific Progress & Innovations, 2015)
The designed thermo-analytical complex in functioning and technical realization of a number of existing prototypes differs from all developed and patented method of formulating the linear law of temperature change of a heater and the use of the combined differential-thermal method of investigating the model and indifferent substance. It uses a precision system for the phase control of average thermal energy supply into the heating zone by program assignment of the proportional, in the course of time, the „development” law of the reference voltage value of the setting device in accordance to temperature characteristics of the chromel-alumel converter with a simultaneous continuous tracking the voltage misbalances Ch-A of thermocouple in the chain of its negative feedback. The complex is simple, with high sensitivity and a good diagnostiсs ability.